Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4172/2161-0444.1000138
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Strategies for Controlling Drug Release by Using Visible/Near IR Light

Abstract: Effective drug delivery systems require controlled drug release at the target cancer cell. While strategies for targeting tumors have been extensively studied, a better understanding of the necessary technology for controlling the spatiotemporal release of a drug is still needed. It has been established that the use of light can be a unique tool for controlling drug release. While UV light can be used for the release of biologically active, caged (deactivated) compounds, clinical application is restricted beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 56 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…Research in the area of PCT that has demonstrated promising results to date includes molecules that photo­sensitize the production of singlet oxygen ( 1 O 2 , commonly known as photo­dynamic therapy agents), compounds that release drugs when irradiated, and transition metal complexes that covalently bind to DNA when photo­lyzed. Although compounds approved for PCT and those currently undergoing clinical trials are almost all organic molecules that produce 1 O 2 upon irradiation, inorganic complexes that possess ligands with extended π-systems and long excited-state lifetimes have been shown to sensitize 1 O 2 with significantly greater efficiency than those currently in use; these species include [Ru(bpy) 2 ­(dppn)] 2+ ( 1 ; bpy = 2,2′-bipyridine, dppn = benzo[ i ]­dipyrido­[3,2- a ;2′,3′- c ]­phenazine), whose structure is schematically depicted in Figure . Upon irradiation with visible light, complex 1 produces 1 O 2 with a quantum yield Φ = 0.88(2) from a long-lived dppn 3 ππ* excited state and efficiently photo­cleaves DNA, but it is not reactive toward the duplex in the dark.…”
Section: Introductionmentioning
confidence: 99%
“…Research in the area of PCT that has demonstrated promising results to date includes molecules that photo­sensitize the production of singlet oxygen ( 1 O 2 , commonly known as photo­dynamic therapy agents), compounds that release drugs when irradiated, and transition metal complexes that covalently bind to DNA when photo­lyzed. Although compounds approved for PCT and those currently undergoing clinical trials are almost all organic molecules that produce 1 O 2 upon irradiation, inorganic complexes that possess ligands with extended π-systems and long excited-state lifetimes have been shown to sensitize 1 O 2 with significantly greater efficiency than those currently in use; these species include [Ru(bpy) 2 ­(dppn)] 2+ ( 1 ; bpy = 2,2′-bipyridine, dppn = benzo[ i ]­dipyrido­[3,2- a ;2′,3′- c ]­phenazine), whose structure is schematically depicted in Figure . Upon irradiation with visible light, complex 1 produces 1 O 2 with a quantum yield Φ = 0.88(2) from a long-lived dppn 3 ππ* excited state and efficiently photo­cleaves DNA, but it is not reactive toward the duplex in the dark.…”
Section: Introductionmentioning
confidence: 99%
“…One study used an Au nanocage containing doxorubicin, which was covered with a polymer to absorb NIR light. 89 The absorption of the light caused the polymer to collapse, releasing the doxorubicin. Another study used peptide-coated Au nanoshells loaded with siRNA to observe how NIR light affected the delivery of siRNA to tumor cells.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…Besides these, techniques based on drug carrier systems have also attracted the attention of researchers. A drug carrier is basically any substrate that aims to improve the selectivity, effectiveness, and/or safety of drug administration, and is primarily used to control the release of a drug into systemic circulation either by the slow release over a longer period or by triggered release at the drug's target by some stimulus, such as changes in pH (Bae et al, ), simple dilution (Stella, Rao, Zannou, & Zia, ), application of heat (Satarkar & Hilt, ), activation by light (Moses & You, ), etc. Drug carrier systems also facilitate the improvement of the basic and essential pharmacokinetic properties, namely water solubility and/or membrane permeability, and hence bioavailability.…”
Section: Introductionmentioning
confidence: 99%